2011
DOI: 10.1111/j.1742-7843.2011.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoisoamyl 2, 3‐Dimercaptosuccinic Acid (MiADMSA) Demonstrates Higher Efficacy by Oral Route in Reversing Arsenic Toxicity: A Pharmacokinetic Approach

Abstract: Monoisoamyl DMSA (MiADMSA), a lipophilic chelating agent has emerged as a promising drug for the treatment of arsenic. The present study aimed at exploring the optimum dose and route of administration for achieving maximum arsenic elimination with minimal side effects. We also carried out a pharmacokinetic analysis of this drug to support arsenic chelation. Rats were exposed to arsenic (25 ppm) for 6 months and later received MiADMSA (50 or 100 mg ⁄ kg) orally and via i.p. route for 5 days. Oxidative stress pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Further repeated administration of MiADMSA was found to be safe in adult rats followed by young and old rats, with female rats slightly more susceptible than males [98]. We also demonstrated that oral administration was more effective than the parental route [41,99,100]. Similarly to our studies, Kreppel et al [101] also reported the superior efficacy of MiADMSA and mono n-amyl DMSA in mice against lethal effects of arsenic.…”
Section: Efficacy and Experimental Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…Further repeated administration of MiADMSA was found to be safe in adult rats followed by young and old rats, with female rats slightly more susceptible than males [98]. We also demonstrated that oral administration was more effective than the parental route [41,99,100]. Similarly to our studies, Kreppel et al [101] also reported the superior efficacy of MiADMSA and mono n-amyl DMSA in mice against lethal effects of arsenic.…”
Section: Efficacy and Experimental Studiessupporting
confidence: 83%
“…Furthermore, pharmacokinetic analysis supported prolonged availability of the drug through oral administration [41]. These findings clearly suggest that oral administration of MiADMSA is more effective than intraperitoneal administration and that the minimum effective dose with the fewest side effects was 50 mg/kg [41]. Generation of free radicals in the case of arsenic toxicity is known to cause cellular apoptosis through a mitochondrial-driven pathway.…”
Section: Efficacy and Experimental Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Also, pharmacokinetic analysis supported prolonged availability of the drug through oral administration. Collectively, these findings led to the conclusion that oral administration of MiADMSA was more effective than intraperitoneal administration and that the minimum effective dose with the least side effects was 50 mg/kg (Flora et al, 2012). Generation of free radicals in case of arsenic toxicity is known to cause cellular apoptosis through a mitochondrial-driven pathway.…”
Section: Monoisoamyl Dmsamentioning
confidence: 96%